Global, regional, and national burden of gout among older adults (≥65) from 1990 to 2021 and projections for 2050 - Xiaoli Tang; Dan Deng; Qian Wu (Frontiers in Public Health)
BackgroundGout, a common and treatable type of inflammatory arthritis, is caused by the buildup of monosodium urate crystals in the synovial fluid and other tissues. This study uses epidemiological modeling to analyze the global impact of gout among older adults (≥65) from 1990 to 2021, with projections extending to 2050, using the most recent data from the Global Burden of Disease (GBD) 2021.MethodData from the GBD 2021 database were used to evaluate the global burden of gout in adults aged 65 and older from 1990 to 2021. The analysis considered factors such as age group (65+), gender, year (1990–2021), geographic classification [204 countries/regions, five socio-demographic index (SDI) regions, 21 GBD regions], and the SDI. Metrics assessed included incidence, prevalence, and disability-adjusted life years (DALYs), with their 95% uncertainty intervals (UI). All metrics were age-standardized using the GBD global standard population.ResultsIn 2021, the global age-standardized incidence rate of gout among older adults was 432.70 (95% UI: 263.28, 677.27) per 100,000 population. The age-standardized prevalence rate was 3,110.84 (95% UI: 2,092.83, 4,419.20) per 100,000, and the age-standardized DALYs were 90.90 (95% UI: 54.95, 139.13) per 100,000 person-years. There was an increasing trend in the incidence rate, prevalence, and DALYs as age increased among those 65 and older. The disease burden among older males was nearly twice that of females. Projections for 2050 show that the age-standardized incidence rate, prevalence rate, and DALYs are expected to increase to 524.99, 3,628.85, and 105.36 per 100,000 population, respectively. Metabolic risks have become the primary risk factor for gout.DiscussionDue to global population aging, our predictive model estimates that by 2050, the number of older adults with gout will increase by 8.5 million. The rise is particularly pronounced in high-SDI and high-income regions, highlighting the need for stronger prevention and management strategies in these areas. Early intervention in metabolic risk factors and improved early diagnosis and treatment are essential for effective gout management.